Islam, Iman, and Ihsan: The Role of Religiosity on Quality of Life and Mental Health of Muslim Undergraduate Students in Islamic University - Abdul Khaiyom, Jamilah Hanum; Tajul Ariffin, Arina Hanis; Md Rosli, Ahmad Nabil (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: The current study examines the relationships between religiosity, quality of life, and positive mental health among Muslim students in an Islamic university in Malaysia. This study uses the operational definition of religiosity based on Hadith Jibril, which defined Islam into three elements: Islam, Iman, and Ihsan. Materials and Methods: One hundred and seventy-nine students participated in this cross-sectional study. Three measures were used to measure religiosity (IIUM Religiosity Scale), quality of life (WHO Quality of Life-BREF Scale), and positive mental health (Positive Mental Health Scale). Results: Significant relationships between religiosity, quality of life, and positive mental health were found. Further analysis found that i) Ihsan highly predicts the physical and psychological domains of quality of life and mental health; ii) Islam shows the highest prediction on social-based quality of life, and iii) Iman highly predicts the environmental-based quality of life. Conclusion: Religiosity plays a vital role in predicting an individual’s quality of life and mental health. These findings provide hope for future research and utilisation of Islamic elements as an intervention for psychological wellbeing among students.